2014
DOI: 10.1242/jeb.096651
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic investigation of underwater hearing capabilities of loggerhead sea turtles (Caretta caretta) using a dual testing approach

Abstract: Sea turtles reside in different acoustic environments with each life history stage and may have different hearing capacity throughout ontogeny. For this study, two independent yet complementary techniques for hearing assessment, i.e. behavioral and electrophysiological audiometry, were employed to (1) measure hearing in post-hatchling and juvenile loggerhead sea turtles Caretta caretta (19-62 cm straight carapace length) to determine whether these migratory turtles exhibit an ontogenetic shift in underwater au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
(76 reference statements)
1
17
0
1
Order By: Relevance
“…Some case studies indicate that the frequency spectrum of hearing in turtles is generally similar in air and under water (e.g. Christensen-Dalsgaard et al 2012;Zeyl & Johnston, 2015;Piniak et al 2016, see also Lavender et al 2014). Extremely little is also known about the function of hearing in turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Some case studies indicate that the frequency spectrum of hearing in turtles is generally similar in air and under water (e.g. Christensen-Dalsgaard et al 2012;Zeyl & Johnston, 2015;Piniak et al 2016, see also Lavender et al 2014). Extremely little is also known about the function of hearing in turtles.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings differ somewhat from those reported elsewhere. For instance, 3-year-old Hawksbill turtles ( Eretmochelys imbricata ) were sensitive to a wider frequency range and exhibited a larger amplitude response than the 2-year-olds [18]; loggerhead sea turtles ( Caretta caretta ) exhibited little difference in threshold sensitivity and frequency bandwidth throughout ontogeny [19]; and in subadult Green turtles ( Chelonia mydas ), smaller individuals had a wider hearing sensitivity bandwidth (100–800□Hz) than larger individuals (100–500□Hz) [17]. Our study improves on earlier studies, potentially providing more reliable results, because we used a larger age range, and, more importantly, we first determined the sex of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been considerable research into auditory system development in some groups of vertebrates, much less is known about it in chelonians. At present, we know of only three studies on the developmental plasticity of hearing sensitivity in chelonians, and these reached different conclusions [17–19]. However, these studies had small samples (n < 7), narrow age ranges, and unclear sexual categorization, factors that may affect their findings.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the loggerhead turtle hotspots is in proximity of the most trafficked highway of the sea, with an annual traffic density of about 2400 vessels/km (Fortuna et al, 2015). Although several national and international management measures have been taken to reduce risks for local population, their effectiveness may be reduced in sea areas with intenisve human activities responsible sea noise pollution (Hildebrand, 2009;Ross, 2005;460 Andrew et al, 2002), that can cause communication masking, stress, hearing loss or habitat abandonment (Nowacek et al, 2007;Clark et al, 2009;Lavender et al, 2014;Nelms et al, 2016). In this context underwater noise pollution mapping (Tasker et al, 2010), has been identified as a major research priority (Maccarrone et al, 2015).…”
mentioning
confidence: 99%